PERSEPSI MAHASISWA TERHADAP PENGEMBANGAN POLITEKNIK PARIWISATA BALI SEBAGAI GREEN CAMPUS - Dewa Ayu Made Lily Dianasari (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
A green campus is a campus that cares about, is environmentally friendly, and has implemented sustainable management. The green campus is also a reflection of the entire academic community who pays attention to aspects of health, work safety, and environmental conditions. The Bali Tourism Polytechnic (Poltekpar) is a tourism university in its development that has made innovations towards the implementation of a green campus. The purpose of the study was to analyze student perceptions of the development of Poltekpar as a green campus in Bali. The survey was conducted on 100 students regarding the implementation of a green campus at the Bali Tourism Polytechnic. The sampling technique was purposive sampling and quota sampling then analyzed by qualitative descriptive method. Students stated that they strongly agreed that the Bali Tourism Polytechnic would become a green campus in terms of the use of electrical energy, water, waste and waste treatment, management of biodiversity and ecosystems, internet connection and transportation. Bali Tourism Polytechnic students want some improvements, are: 22% for offices and classrooms, 21% for waste and sewage treatment, 15% each for green open land and electrical energy, 12% for IT, 6% for water resources, 5% for transportation and 4% for laboratory repairs.